Transient micropaleontological turnover across a late Eocene (Priabonian) carbon and oxygen isotope shift on Blake Nose (NW Atlantic) - J. de Entrambasaguas; J. de Entrambasaguas; T. Westerhold; H. L. Jones; L. Alegret; L. Alegret (Journal of Micropalaeontology, 2024)
The Gulf Stream, a western boundary current transporting warm water into the North Atlantic, plays a key role in climate regulation and oceanographic stability at a regional and global scale as part of the Atlantic Meridional Overturning Circulation (AMOC). Evidence suggests that an ancestral Gulf Stream has existed since the Mesozoic, and it has altered its course repeatedly over Cenozoic times. In this study, we focus on the upper Eocene (Priabonian, ca. 36 Ma) from Ocean Drilling Program Site 1053 on Blake Nose (subtropical North Atlantic). Bulk carbon and oxygen stable isotopes, as well as benthic foraminiferal and calcareous nannofossil assemblages, provide an integrated assessment of the palaeoceanographic changes impacting the area through the water column to the seafloor. Micropaleontological assemblages suggest changes in surface ocean stratification and nutrient supply to the seafloor coeval with a paired negative carbon and oxygen isotope excursion and the return to background conditions higher up in the study section. These transitory changes are compatible with the longitudinal displacement of the proto-Gulf Stream and its related eddies. Our results build on previous work and support the hypothesis that links palaeoceanographic changes in the Blake Nose area with shifts in the proto-Gulf Stream during the middle and late Eocene.